The Trade between the countries of the pacific alliance. An analysis from the gravitational model and the bilateral exchange (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
At present, the Pacific Alliance is consolidated as the first economic bloc in Latin America. The stylized facts of international trade have shown that national production and distance are crucial elements to define export volume. This article aims to show the evolution of bilateral trade in Colombia with the other three co-founders of the Alliance, within the framework of a gravity model applied to the exchange of goods. It is concluded that the volume of exports is systematically directly related to the size of the market represented in the Gross Domestic Product (national production), and inverse with the physical distance and the associated transport costs. These aspects, together with an analysis of the trade balance of each country in the last decade, intend to outline some potentialities of the Colombian economy after said commercial integration; given that while it maintains a trade deficit with the Alliance as a whole, with two of the countries its bilateral relationship is surplus.
Keywords: gravitational model; economic integration; international trade